Restricted diets, micronutrient intake, and nutritional status - Eveleigh, Elizabeth (2023)
Iodine deficiency in the UK has re-emerged in vulnerable groups. Dietary iodine has an essential role in the formation of thyroid hormones which regulate growth and metabolism. Iodine deficiency is particularly problematic for women of childbearing age and those who are pregnant and/or lactating as optimal thyroid function is vital for foetal neurodevelopment. Today, iodine deficiency is still considered the biggest single preventable cause of brain damage globally (WHO, 2007).